Tourism or sustainable tourism in the Global South? Perspectives from Guinea-Bissau - Andreia Martins; Claudete Oliveira Moreira (Via@)
Tourism in the Global South is a vital economic activity that promotes development, but many countries, like Guinea-Bissau, face significant challenges due to political, economic, social, and environmental fragility. This study aims to analyse stakeholders’ perception and expectations of tourism's potential to catalyze sustainable development, identify reasons why Least Developed Countries (LDC) may fail to achieve it, and present both positive and negative impacts of tourism. The study involved 21 semi-structured interviews, and the Quintuple Helix Model to analyze stakeholders' perspectives. The results indicated that: tourism stakeholders in Guinea-Bissau agree that while tourism can provide jobs, attract investment, and improve infrastructure, local populations also face challenges in appropriating these benefits due to limited development, political instability, and unfavourable governance. To achieve sustainability, responsible tourism must be promoted among stakeholders, influencing investment and travel patterns. Addressing these issues can help optimize their contribution to development and promote responsible tourism.